PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, DAN NET INTEREST MARGIN TERHADAP HARGA SAHAM PERBANKAN MILIK NEGARA (Studi Kasus Pada Bank BNI (Persero) Tbk dan Bank BTN (Persero) Tbk Periode 2014-2018) - Utami Nugraha Putri, Tri; Astuti, Nelly; Ahmad Agin, Arka’a (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
This is an undergradate thesis is written and compiled by Tri Utami Nugraha Putri (student id 540150018). The thesis entitled in Indonesian language; “Pengaruh Capital Adequacy Ratio, Non Performing Loan, dan Net Interest Mrgin Terhadap Harga Saham Perbankan Milik Negara (Studi Kasus Bank Tabungan (Persero) Tbk dan Bank Tabungan Negara (Persero) Tbk Periode 2014-2018”This research was conducted from February to July 2019 at the Stie Ibek Campus in Pangkal Pinang city.The population in this study were state-owned banking companies listed on the Indonesia Stock Exchange in 2014-2018. But this research only focuses on two banks which are used as research samples, namely at Bank Negara Indonesia (Persero) Tbk, and the Bank Tabungan Negara (Persero) Tbk.In this study using a multicollinearity test method, multiple regression analysis, coefficient of determination, and hypothetical test. Based on the results of the research in the partial t test prove that Capital Adequacy Ratio, Non Performing Loan, and Net Interest Margin have a positive effect on Stock Prices. and the F test proves that Capital Adequacy Ratio, Non Performing Loan, and Net Interest Margin have a simultaneous effect on stock prices. Based on the calculation of Fcount 28.44 greater than f table 8,245with a significant value of 0.015